Thermodynamics of (NH4 +) cation adsorption under static conditions - Sabadash, Vira; Gumnitsky, Jaroslaw; Lyuta, Oksana; Pochapska, Iryna (Lviv Politechnic Publishing House, 2018)
Експериментально досліджено адсорбцію йонів амонію природним цеолітом та Al2O3 за статичних умов. Обґрунтовано причину зміни рН досліджуваного розчину під час адсорбції йонів амонію на Al2O3. Побудовано діаграму складу двокомпонентної системи і встановлено склад адсорб- ційної системи в стані рівноваги. Здійснено термодинамічні розрахунки адсорбційної системи Al2O3–NH4Cl–H2O. Вста- новлено, що поглинання амонію оксидом алюмінію відбувається за механізмом фізичної адсорбції.

The adsorption of ammonium ions by natural zeolite and Al2O3 under static conditions has been investigated. The reason for changing the investigated solution pH during adsorption of ammonium ions on Al2O3 has been grounded. A phase diagram of the twocomponent system has been constructed and the composition of the adsorption system in the state of equilibrium has been determined. The thermodynamic calculations of the adsorption system Al2O3–NH4Cl–H2O have been carried out. It was established that the adsorption of ammonium with aluminum oxide occurs via the mechanism of physical adsorption.
Термодинаміка адсорбції катіонів (NH4+) на Al2O3 за статичних умов
Keywords: адсорбція; термодинаміка; йони амонію; цеоліт; Al2O3; adsorption; thermodynamics; ammonium ions; zeolite; Al2O3